Training and Human Resource Development Methods and Effectiveness - Aria Elshifa; Tungga Buana Irfana; Sri Hardianty; Ikram Yakin; Muhammad Yusup (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Human Resource (HR) training and development is a strategic aspect in improving organisational performance and competitiveness. This research aims to explore the training methods used by organisations and evaluate their effectiveness in improving employee competencies. This research uses a qualitative approach with a case study design in a multinational company in Jakarta. Data was collected through in-depth interviews, participatory observation, and document analysis from 15 employees who had attended the training programmed. The results showed that the company uses various training methods, such as simulation, technology-based training, and mentoring. The effectiveness of the training varies depending on the relevance of the material, the involvement of the instructor, and the contextualisation of the programme to the needs of the employees. The main supporting factors are the availability of resources and management commitment, while barriers include the lack of personalisation of the programmed and inflexible schedules. The study concludes that training effectiveness is influenced by the suitability of methods to individual and organisational needs. Recommendations include improved training needs analysis, adoption of interactive learning technologies, and continuous evaluation to ensure skills application on the job.